Strategi Pengembangan Usaha Ternak Sapi Perah di Desa Benlutu (Study Kasus Novisiat Claretian Benlutu) - Kollo, Ronaldus; Lole, Ulrikus R.; Krova, Maria (Animal Agricultura, 2025)
This study aims to formulate development strategies for the dairy cattle business at the Claretian Benlutu Novitiate Monastery, Timor Tengah Selatan Regency. A case study survey approach was employed, utilizing primary data from observations and interviews, and secondary data from relevant institutional documentation. SWOT analysis was applied to assess internal and external factors, which were then mapped using the IFE and EFE matrices. Results indicate positive scores on both matrices, positioning the dairy cattle business in Quadrant I, signifying a highly favorable condition for aggressive development. QSPM analysis identified three main strategic priorities, expanding the scale of the dairy cattle business, improving the quality and productivity of fresh milk, and optimizing internal resource utilization while reducing vulnerability to external factors. These strategies are recommended to strengthen competitiveness and ensure the sustainability of the dairy cattle enterprise in the study area.